Insights into the Positive Role of a Higher Education Institution in the Prevention of Misinformation During Pandemics: The Health Committee Model During COVID-19 - Halat, Dalal H.; Akel, Marwan; Hajj, Fatima; HajjHussein, Hassan; Kansoun, Rawad; Sharif-Askari, Ehsan; Siblani, Lama; Faraj, Ahmad (Coronaviruses, 2021)
In Lebanon, with COVID-19 cases escalating and national efforts exhausted in the containment of the pandemic, calls were made for increased awareness, scientific literacy, and the debunking of false information. This article sheds light on the positive role that a private University can play in spreading scientifically-authenticated, health-related, awareness through the community. The Lebanese International University (LIU) has 9 campuses distributed across all Lebanese Governorates with an extensive communications platform that takes advantage of LIU’s website, University Management System, several Facebook pages with thousands of followers, and many WhatsApp groups. LIU has over 34,000 undergraduate and graduate students, in addition to a little over a thousand faculty and staff members. The University capitalized on this extensive network to play a positive role in delivering authenticated health-related information to the University’s greater community. A health committee comprised of multidisciplinary educators, mostly from the fields of medicine and health sciences, was established to act as a health advisory panel to the University Council and to raise awareness among the University’s larger community. An extensive health awareness campaign was launched through activities and the sharing of the material of different formats aimed at providing accurate information on infection prevention, and disseminating authentic and accurate health-related guidelines and recommendations during the pandemic. This compendium aims to summarize the role of the health committee in meeting the various challenges created by the emergence of COVID-19 in our community, and highlights its influence and future perspectives.
Keywords: university